THE MAIN TRENDS IN THE DEVELOPMENT OF THE AUTOMOTIVE INDUSTRY AND THE TECHNICAL OPERATION OF CARS - Anvar Uralbayev (American Journals, 2023)
The article describes that one of the most important problems facing road transport is to increase the operational reliability of cars. It also considers ensuring the operability and realization of the potential properties of the car, incorporated during its creation (in particular, operational reliability), reducing the cost of maintenance and repair, and reducing the corresponding downtime. Ensuring an increase in the productivity of transportation while reducing their cost, that is, increasing efficiency and ensuring environmental friendliness are the main tasks of the technical operation of the rolling stock of road transport.
Keywords: technical operation, car, resource, transportation, service, transport repair.